Engineering of bamboo fiber and glass fiber composites with B₄C filler for fire-resistant structural material applications - Andika Rafi Ryansyah; Andoko Andoko; Riduwan Prasetya (Politeknik Negeri Lhokseumawe, 2026)
The increasing demand for lightweight, high-strength, and fire-resistant materials has driven the development of hybrid epoxy composites reinforced with bamboo fibre (SB) and glass fibre (SK), incorporating boron carbide (B₄C) as a functional filler. This study investigates the effects of composition and B₄C content on the physical, mechanical, and fire-resistant properties of hybrid epoxy composites. Four formulations (100E, 70E30SB, 70E30SK, and 70E15SB15SK) were prepared with B₄C contents of 0, 2.5, and 5 wt%. The composites were evaluated for density, tensile strength, elongation, impact strength, Shore-D hardness, and fire resistance (limiting oxygen index (LOI), char yield, and burning rate). The results show that density increases with increasing B₄C content. A filler content of 2.5 wt% provides the most consistent improvement in mechanical properties, with the highest tensile strength observed in the 70E30SK composite (317 MPa). However, increasing the B₄C content to 5 wt% reduces several mechanical properties due to particle agglomeration. In the Shore-D hardness test, an increase is observed in 70E30SB, while 70E30SK and 70E15SB15SK decrease at 2.5 wt% B₄C before increasing again at 5 wt%. In impact testing, 70E30SK shows the highest toughness without B₄C, whereas 70E30SB and 70E15SB15SK improve at 5 wt% B₄C. In terms of flammability, B₄C increases the LOI and reduces the burning rate, particularly in glass fibre-rich composites, although changes in char yield are not always significant. Overall, B₄C improves fire resistance and can enhance mechanical performance when dispersed under optimal conditions.